Phase change memory cell emulator circuit design. (April 2017) - El-Hassan, Nemat H.; Kumar, T. Nandha; Almurib, Haider Abbas F.
Abstract: This paper presents a novel phase change memory (PCM) cell emulator circuit design created solely with off-the-shelf discrete electronic components. The designed emulator circuit reproduces PCM cell behavior in terms of temperature across the cell, threshold voltage, and programmed resistance levels in response to a given input. The presented circuit is designed and tested in simulation environment using LTSpice. The circuit was then built with CMOS 0.35 µm technology along with other off-the-shelf discrete components. The designed emulator circuit successfully generated the operational features of a PCM cell. The emulator circuit assessed the impact of the programming time, produced the standard I-V characteristics of a PCM element and retained the stored data throughout the duration of operation. Furthermore, the simulation and experimental results of the designed emulator circuit were found to be in close agreement with the experimental data obtained from an actual Ge2 Sb2 Te5 (GST) based PCM element.